An evaluation of the Center for Educational Measurement Degree Program in Guidance, 1983-86 - Llanes, Rosa Maria I. (Animo Repository, 1988)
This study is a summative evaluation of the Center for Educational Measurement Degree Program in Guidance. The question intended to be answered was: How effective is the delivery system of guidance services as implemented by the grantee guidance counselors? The specific questions intended to be answered by this study were (a) adequacy of the counselor-training program, (b) effectiveness of the guidance services as perceived by the students, faculty and administrators and (c) adequacy of the grantees in the delivery of guidance services. This study used the descriptive method of research. Five questionnaires were fielded to the following respondents: (1) host institution, (2) administrator, (3) faculty, (4) grantee, and (5) student. Mean ratings and percentages were computed. The results are as follows. The screening scheme and grantee preparedness for the program were rated as very satisfactory. The financial grant from CEM was appraised as very satisfactory while that from the grantee school, satisfactory. The three host schools used, namely: (a) De La Salle University, (b) University of San Carlos and (c) Ateneo de Davao were assessed on several factors. The following factors were all rated as very satisfactory, namely: (a) physical plant and facilities, (b) library resources, (c) personnel, and (d) teacher-student ratio. The performance of the professors was rated as excellent. The curriculum was rated as very satisfactory. The core subjects, cognates and practicum were all very satisfactory. The most difficult subjects were Testing, Research and Techniques of Counseling, while the easiest were the cognates. The most relevant was Organization of Guidance Services and the least relevant was the thesis. The most useful subject was Techniques of Counseling and the least useful was the thesis. The CEM member schools have been rated as having very satisfactory organizational set-ups in their guidance offices. The physical facilities were rated as very satisfactory as to adequacy and accessibility. A counseling room was provided as claimed by 91 percent of the respondents. The grantee/guidance counselors were rated as very satisfactory in terms of competence. The ratio of guidance counselors to students was 1:1129. The teachers as partners in the guidance program implementation also performed their role at a satisfactory level though slightly lower than their role awareness level which was very satisfactory. The administrative support was reported as very satisfactory. The aspects which were rated as very satisfactory were the following: (a) selection of grantees, (b) orientation of grantees, (c) coordination among the CEM, host schools, CEM member schools, (d) preparation of grantees for the practicum, and (e) evaluation of student achievement. Two areas received satisfactory ratings: (a) orientation of grantees and host schools on the program and (b) practicum supervision. In terms of effectiveness of the delivery of services, the ranking was as follows: (a) placement, (b) inventory, (c) follow-up, (d) testing, (e) counseling, (f) referral, (g) research, and (h) information. The first five services obtained very satisfactory ratings while the last three got satisfactory ratings. Guidance program dissemination was carried satisfactorily through: (a) orientation, (b) posters, and (c) school newspapers with the help of the guidance counselors, teachers, and school heads.